Contribuição do fenótipo para o diagnóstico de síndromes de microdeleções por meio de metodologia adequada à realidade brasileira - Melissa Machado Viana (2013)
Medical Genetics specializes in disorders with congenital malformations, developmental delay and cognitive impairment, which can be individually rare, but that affect a considerable number of individuals and families when put together. Diagnosis is an important part of the genetic approach, since accurate diagnosis is essential to chose a specific treatment, to establish a clinical prognosis, to guide parents about the progress of the disease and possible complications and to define reproductive prognosis for the family, based on the risk of recurrence in future pregnancies. Currently, it is not possible to establish an etiologic diagnosis in cases of mental retardation/developmental delay with or without congenital anomalies in 40-60% of genetic patients. Diagnostic methods in genetics can be divided into two categories: those directed to the whole genome (broad diagnosis) and those that are geared to a specific DNA region (targeted diagnosis). Broad techniques allow a full assessment of the genome. However, those techniques with high resolution are expensive and prohibitive for the scenario of emerging economies such as Brazil. Targeted techniques are more feasible for countries with limited resources. It is more logical and cheaper to have a clinical suspicion and then indicate a specific diagnostic test than performing a scan of the entire human genome in search of a abnormality. In this context, clinical assessment by a physician and phenotype determination are critical. Microdeletion/microduplication syndromes are caused by submicroscopic copy number variants of a particular region of the genome and are a common cause of congenital anomalies, developmental delay/cognitive deficit and neuropsychiatric disorders. The present study aims to evaluate the phenotype contribution in the identification and diagnosis of patients with microdeletion/microduplication syndromes in Minas Gerais/Brazil, thus allowing to use targeted technologies that are cheaper and more appropriate to Brazilian reality. Between 2005 and 2012, 3,239 patients were evaluated for the first time at Serviço Especial de Genética Médica do Hospital das Clínicas da UFMG. Of these, 205 (6.3%) had suggestive clinical features of one of the microdeletion/microduplication syndromes included in this survey. A total of 150 patients formed the group to be studied (loss rate of 26.8%). Of these, 37 were positive for one of the syndromes, giving an overall diagnostic yield of 24.7%. We used a new, fast, reliable and low cost method for detection of microdeletion and microduplication syndromes in humans, called Microdeletion/Microduplication Quantitative Fluorescent Polymerase Chain Reaction (MQF-PCR). The best results were obtained with Williams syndrome (diagnostic yield of 63.6%), Prader-Willi syndrome (diagnostic yield of 41.7%), Angelman syndrome (20%) and Velocardiofacial syndrome (12.9%). The approach used in this research (phenotype assoiated with a targeted test) proved to be suitable for Brazil, especially for patients with the above syndromes. These are diseases in which phenotype was a usefull tool for the diagnosis.